2021
DOI: 10.1093/treephys/tpab031
|View full text |Cite
|
Sign up to set email alerts
|

Cork cells in cork oak periderms undergo programmed cell death and proanthocyanidin deposition

Abstract: Vascular plants with secondary growth develop a periderm mostly composed of dead suberized cork cells to face environmental hostile conditions. Cork oak has a highly active and long-living phellogen forming a remarkably thick periderm that is periodically debarked for industrial purposes. This wounding originates the quick formation of a new traumatic periderm, making cork oak an exceptional model to study the first periderm differentiation during normal development in young sprigs and traumatic (wound) peride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…These are polyphenolic secondary metabolites synthesized as oligomers or polymers via the flavonoid pathway (Sagasser et al 2002, Appelhagen et al 2010, 2011. We can hypothesize that the strongly expressed WIP3 is specially involved in the control of flavonoid and tannin accumulation, expected in the new cork oak phellem cells (Graça and Pereira 2004, Silva et al 2005, Inácio et al 2021, or other new secondary tissues (Crang et al 2018). Also in mature cork oak roots we detected the expression of TFs described as the first layer of regulation for secondary cell walls, such as the VND1/3/4 (LOC111996673/LOC111994497/LOC112007201, LOC111988979) and XND1 (LOC112009005) homologs (Zhang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These are polyphenolic secondary metabolites synthesized as oligomers or polymers via the flavonoid pathway (Sagasser et al 2002, Appelhagen et al 2010, 2011. We can hypothesize that the strongly expressed WIP3 is specially involved in the control of flavonoid and tannin accumulation, expected in the new cork oak phellem cells (Graça and Pereira 2004, Silva et al 2005, Inácio et al 2021, or other new secondary tissues (Crang et al 2018). Also in mature cork oak roots we detected the expression of TFs described as the first layer of regulation for secondary cell walls, such as the VND1/3/4 (LOC111996673/LOC111994497/LOC112007201, LOC111988979) and XND1 (LOC112009005) homologs (Zhang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Further down the phenylpropanoid pathway acting in the early steps of the lignin branch, the enzyme hydroxycinnamoyltransferase (HCT) whose corresponding gene, when down-regulated, leads to a strong decrease of suberin-linked ferulic acid levels [ 77 ]. Proanthocyanidins (PA), the end product of the flavonoid pathway, a phenylpropanoid pathway branch [ 78 ], accumulates in the vacuoles of cells of the traumatic periderms and young cork cells, and associate with the cell walls of suberized empty cells [ 79 ]. Anatomy studies have already shown us that the first cork cells formed can be distinguished by their electrodense fillings and brown inclusion of tannins [ 18 ], a feature also observed in cork oak’s one-year stems [ 42 ] ( Figure 2 j).…”
Section: Molecular Basis Of Cork Developmentmentioning
confidence: 99%
“…Suberin, lignin and polyphenol production are amongst the most enriched categories during cork tissue development, but autophagy and programmed cell death (PCD) are also categories with high number of up-regulated genes [ 79 ]. Besides the high suberin content of periderm cork cells, another characteristic of these cells is the fact they are dead by the time functional maturity is reached, implying they undergo PCD [ 84 ].…”
Section: Molecular Basis Of Cork Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The periderm formation involves several processes: phellogen initiation and cell proliferation, radial cell elongation, secondary cell wall formation through the deposition of suberin and waxes, and dPCD (Inácio et al, 2021;Serra et al, 2022). Despite the enormous progress in understanding the molecular mechanisms underlying vascular cambium regulation, very few regulators or potential regulators of phellogen activity and phellem differentiation have been identified (Miguel et al, 2016;Verdaguer et al, 2016;Xiao et al, 2020;Ye et al, 2021).…”
Section: Epigenetic Evidence In Periderm Developmentmentioning
confidence: 99%